Nutrient Intake, Growth and Blood Parameters of West African Dwarf goats fed Composite Diets Comprising of Rumen Waste, Poultry Waste and Cassava Peels - Inweh, D. A.; Ikhatua U. J.; Bamikole M. A. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
Rumen waste (RW), poultry waste (PW) and cassava peels (CP) are readily available in most agro industrial areas in Nigeria and harnessing them as feeds for West African dwarf goats will be of immense benefit to farmers. This study was undertaken to ascertain effects of feeding composite diets comprising of rumen waste, poultry waste and cassava peels on nutrient intake, growth and blood parameters of West African Dwarf goats. Four experimental diets were formulated with diet 1 (control) containing conventional feed materials while diets 2, 3 and 4 contained the wastes in varying proportions of 5, 15, and 25%. The goats were given a basal diet of concentrate containing brewer’s dried grain (BDG), vitamin/mineral salt mixtures and Panicum maximum. Chemical composition of the diets showed no significant (P > 0.05) differences in nutritional composition, except diet 3, which had higher (P < 0.05) values of Crude Protein (21.00 %) and NDF (61.00 %).  Diets 2 and 3 had the least (P < 0.05) Metabolizable Energy of 3.91 and 5.65 MJ/Kg DM, respectively. Results of feeding trial showed significantly (P < 0.05) low nutrient intake for composite diets 2, 3 and 4 compared to diet 1 (control diet). Growth performance result showed that goats on diets 1 and 4 significantly (P < 0.05) gained more weight (1.07kg and 0.97kg respectively), while goats on diet 2 and 3 significantly (P < 0.05) lost weight (-1.63kg and -0.56kg respectively). Poor acceptability of diets 2 (5% RW, 15% PW and 25% CP) and 3 (15% RW, 25% PW and 5% CP) resulted in poor growth of goats on these diets. But diet 4 (25% RW, 5% PW and 25% CP) with lower nutrient intake compared to diet 1 (control), had a higher (P>0.05) feed conversion efficiency (FCE) of 0.14 compared to 0.07 for the latter. This was indicated in the weight gain of goats on diet 4 being comparable to those on 1 (0.97kg and 1.07kg respectively). Packed cell volume (PCV) and blood glucose were low for all diets, while urea levels were high. Therefore, an appropriate proportion of these wastes as in diet 4 (25% RW, 5% PW and 25% CP), ensuring adequate nutrition can be used to feed small ruminants.